1984
DOI: 10.1128/jb.159.2.570-578.1984
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli K-12 outer membrane protein (OmpA) as a bacteriophage receptor: analysis of mutant genes expressing altered proteins

Abstract: The outer membrane protein OmpA of Escherichia coli K-12 serves as a receptor for a number of T-even-like phages. We have isolated a series of ompA mutants which are resistant to such phages but which still produce the OmpA protein. None of the mutants was able to either irreversibly or reversibly bind the phage with which they had been selected. Also, the OmpA protein is required for the action of colicins K and L and for the stabilization of mating aggregates in conjugation. Conjugal proficiency was unaltere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
87
0
2

Year Published

1985
1985
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(97 citation statements)
references
References 66 publications
8
87
0
2
Order By: Relevance
“…It could be the result of different genes experiencing different evolutionary pressures. For instance, gaps in the sequence alignment suggest that the ompA gene has experienced relatively strong selective pressure, presumably from bacteriophage such as K3 and Ox2, which have been shown to bind to the surface exposed loops of OmpA (Manning et al, 1976;Morona et al, 1984). Alternatively, the gene trees may differ because LGT has resulted in different phylogenetic histories for the different genes.…”
Section: Discussionmentioning
confidence: 99%
“…It could be the result of different genes experiencing different evolutionary pressures. For instance, gaps in the sequence alignment suggest that the ompA gene has experienced relatively strong selective pressure, presumably from bacteriophage such as K3 and Ox2, which have been shown to bind to the surface exposed loops of OmpA (Manning et al, 1976;Morona et al, 1984). Alternatively, the gene trees may differ because LGT has resulted in different phylogenetic histories for the different genes.…”
Section: Discussionmentioning
confidence: 99%
“…It was recognized soon after its discovery that it is a receptor for several bacteriophages, particularly phages K3, Ox2 and M1 (Schwarz et al, 1983;Morona et al, 1984;Riede et al, 1984;Montag et al, 1987). The p38 tail fibre protein of these viruses recognize OmpA through its surface-exposed loops 1, 2 and 3 (Morona et al, 1984(Morona et al, , 1985Koebnik, 1999). Recently, Power et al (2006) have identified two alleles of ompA, ompA1 and ompA2.…”
Section: Functions and Properties Of Ompamentioning
confidence: 99%
“…The bacteria were grown at 37°C with shaking (250 rpm), unless stated otherwise. The phage K3 [8,9] was propagated on the E. coli K-12 strain 701 [12], and treated with 0.5% Sarkosyl (N-lauroylsarcosine sodium salt, Sigma) which was subsequently replaced with 0.1% Triton X-100 by linear sucrose (5-20% w/w) gradient centrifugation (75 000 × g for 50 min at 10°C). The fraction with phage was diluted with antibiotic medium 3 as indicated.…”
Section: Organisms and Growth Conditionsmentioning
confidence: 99%
“…The adjacent membrane-spanning/3-strands of OmpA form four surface loops around amino acid residues 25, 70, 110 and 154 [5]. These loops act as receptors for specific bacteriophage [8,9] and they are also needed to stabilize mating aggregates in F-mediated conjugation [8,10]. The /3-barrel structure applies only to the amino acid residues 1 to approx.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation